2019
DOI: 10.3390/en12112093
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation Investigation on the Windage Power Loss of a High-Speed Face Gear Drive

Abstract: Reducing the energy consumption and improving the efficiency of high-speed transmission systems are increasingly common goals; the windage power loss is not negligible in these methods. In this work, the multi-reference frame (MRF) and periodic boundary conditions (PBC) based on the computational fluid dynamics (CFD) method were adopted to investigate the windage phenomena of a single face gear with and without a shroud, and the impact of the gear speed on the windage power loss was analyzed. Furthermore, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Therefore, the two-equation SST k-ω model, suitable for high Reynolds numbers, is selected in this study; this model can more accurately predict the resistance and separation effects of teeth on airflow. The turbulent kinetic energy k of this model and its dissipation rate ω satisfy the following transport equation [2,4,21,26,29]:…”
Section: Simulation and Computational Models 21 Turbulence Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the two-equation SST k-ω model, suitable for high Reynolds numbers, is selected in this study; this model can more accurately predict the resistance and separation effects of teeth on airflow. The turbulent kinetic energy k of this model and its dissipation rate ω satisfy the following transport equation [2,4,21,26,29]:…”
Section: Simulation and Computational Models 21 Turbulence Modelmentioning
confidence: 99%
“…When the linear speed of the gear is too large, the turbulent flow field distribution in the gear box is complicated, which will produce a large windage moment. A windage moment includes a pressure moment and a viscous moment, of which the pressure moment accounts for the largest proportion [1][2][3][4][5] and can account for more than 90% of the total moment. The power loss caused by the windage moment plays an important role in the total power loss of high-speed gears [6][7][8], and both the windage moment and windage power loss increase exponentially with the increase in the gear speed [9][10][11]; that is, the windage loss of gears cannot be ignored under high-speed conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Fondelli et al 10 conducted a numerical study on the WPL of a single spur gear rotating in an oil-free environment, and inferred that the fluid volume inside the box affected the WPL. Dai et al 11 studied the WPL of a single face gear with and without a shroud, analyzed the influence of gear speed on the WPL, and demonstrated that gear speed had a significant influence on the WPL. He et al 12 studied the influence of shrouds on gear WPL by comparing a smooth shroud and groove shroud in their investigation.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the main numerical strategies so far are the MRF-Multiple Reference Frame method (i.e. 'Frozen Rotor') (Concli & Gorla, 2016;Dai et al, 2019;Zhu et al, 2020a) for steady computation, the sliding mesh method (also known as 'Transient Rotor Stator') (Concli et al, 2015) for transient analysis, the mesh morphing (Qi et al, 2016) and the remeshing (Concli et al, 2013, september;Gorla et al, 2013). However, the first two are limited to simulate an isolated spinning gear, while the latter two can handle the gear engagement.…”
Section: Introductionmentioning
confidence: 99%